The application of geographic information systems (GIS) in the development of a suitability index for prospecting tetrapod fossils in the municipality of Lourinhã (Zubía, 2024)
Paleontological prospection campaigns are traditionally planned aroundprevious knowledge of sites that have provided fossils and the interpretationof the regional geology. The application of a suitability index developed forthe study of other rock formations (e.g. Two Medicine Formation, in Canadaand USA) in the Upper Jurassic deposits of the Lourinhã municipality (Portugal), we determined areas with a higher likelihood of providing tetrapodfossils. The index was built using geospatial data, and through the usage ofa weighted sum it was possible to determine the values of the suitability index, and then project them unto a map of the municipality of Lourinhã. Thetotal area of the municipality was divided according to different suitabilityindexes: lower (overall area of 29,55 km2), medium (overall area of 78,56km2) and higher (overall area of 39 km2). The application of these methodsallows considering distinct factors beyond the geology that can speed up thedecision-making process for prospecting and land management.